Healthful Practices Among Blood Donors in a Low-Income Setting - Samuel Amo-Tachie; Yvonne Dei-Adomokoh (University Library System, University of Pittsburgh, 2023)
Background: Blood donation is sustained by the availability of healthy donors. It does not only require recruiting new healthy donors, but also maintaining existing ones in optimal health. As recruitment of new donors is not guaranteed, it is essential that existing donors are always in good shape. The study therefore assesses the lifestyles and healthy habits of a sample of recurrent blood donors, their demographic characteristics, and motivations for donation. Methods: This was a cross-sectional study involving 127 blood donors between the ages of 17 and 60 years in Korle-bu, Ghana. Participants were sampled by the snowball method and administered pre-tested electronic questionnaires. The data was summarised using the Numbers software by Apple Inc. and then analysed. Results: All were non-smokers and engaged conscientiously in at least one healthy habit of a sort, with 60.3% actively following fitness schedules. There were no lifestyle-related health conditions or substance addictions. Up to 94% of the respondents had attained university education. Motivations for donations revolved mostly around altruism and almost half (46.5%) of the respondents conceded that being blood donors had made them live healthier. Conclusion: Voluntary blood donors in the selected low-income setting were mostly health conscious, and the donor status significantly affected this way of life, only more indirectly than directly. More indirectly because the healthy habits practised were predominantly personal well-being oriented but reinforced by the desire to donate blood in many situations.